Functionality of a Technical University Teacher: Targets - D. P. Danilaev; N. N. Malivanov (Moscow Polytechnic University, 2023)
The university teachers' tasks are being updated, their labor functions are being revised and supplemente, with changes at the higher education system. The good organization of a modern university teacher is subject to numerous external targets. The perception of these targets, as well as the personal value of the activity components, are important. The purpose of the article are the identification of tasks for a technical university teacher from the standpoint of the Higher School strategic targets, and determination of their solution limitations. The paper reveals the strategic tasks hierarchy of higher technical education - for technical universities, departments and their teachers; the academic community attitude review to strategic objectives is carried out (including: how the strategic objectives are understood by teachers, how priorities and emphasis are placed in these tasks); the priorities of technical universities teachers are evaluated in terms of their tasks solving; restrictions are indicated in solving these problems, and these restrictions connection with the working conditions of the technical universities teaching staff. The paper points out the balancing problem of the teachers work, and the emerging dissonance among the goals, tasks set for them, and private indicators of their activities effectiveness. The engineering education strategic goals and objectives should proceed from the fact, that this is a mutually responsible process of the qualified technical specialists training, from the authors' point of view. This is especially topical for the returning process to the engineers training.